Biochemical and thermal analysis of spirulina biomass through FTIR, TGA, CHN - Soni, R. A.; Sudhakar, K.; Rana, R. S. (Tech Science Press, 2021)
Spirulina is a sort of algae that grows in both fresh and seawater. It is considered the Earth’s most nutritionally dense food. Certain claims about Spirulina’s beneficial health properties are attributed to the relatively high protein content of the cells. Spirulina’s lipid, fatty acid profile, and biochemical composition have received little atten-tion. The purpose of this study is to investigate the nature and decomposition of spirulina biomass at various temperatures. In the present investigation, Fourier transforms infrared spectroscopy, thermogravimetric analysis, and elemental analysis were used to study spirulina biomass biochemical characteristics. The optimal content of spirulina protein, lipid, and the amino acid was identified and reported. In this study, the various frequency ranges corresponding to functional groups are evaluated and reported. Spirulina FT-IR spectra were recorded and reported at different frequency ranges from 3870–3448 cm−1 to 695–545 cm−1. FTIR studies for spirulina bio-mass affirmed the occurrence of –OH, –COOH, NH, C–H, and C=O groups. Protein (3453 and 1645 cm−1) and carbohydrate (1032 and 1033 cm−1) were the main components with distinct IR spectra fingerprint characteristics. Results indicate that Spirulina sp. biomass is viable green energy and the biggest protein source. The mechanism underlying the high rate of protein accumulation of spirulina may aid in not only elucidating the biochemistry but also in modifying the chemical composition and strain selection for the production of specific chemicals and products.